Peningkatan Kinerja UMKM melalui Pelatihan Manajemen Sumber Daya Manusia Berbasis Kompetensi - Pribadi, Teddy; Marbun, Patar; anjarnahor, Marali (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service activity, themed "Improving MSME Performance Through Competency-Based Human Resource Management Training," aims to improve MSMEs' understanding and skills in managing human resources effectively. This program includes training, mentoring, and the implementation of HR management functions such as recruitment, competency development, and performance evaluation, using a creative economy-based approach. Human Resource (HR) competency is crucial in an organization. Improving competency supports organizational strategy. Having a business strategy is crucial for survival in today's competitive climate. With these two components, it is hoped that MSME employees can maximize their performance and sustain their businesses. The activity involved identifying MSME needs, developing applicable training materials, and evaluating implementation results in the field. The results demonstrated an increase in MSME awareness and ability to strategically manage HR, leading to improved competency.